Development of Learning Video on Mushroom Material for Students of Grade X MIA 5 MAN 1 Makassar City - Muhammad Al Gazali; Adnan Adnan; Andi Mu’nisa (Universitas Negeri Makassar, 2023)
Abstract. Learning videos on mushrooms for class X students were developed with the aim of producing learning media that are valid and practical. The learning videos on mushroom material that are developed have a short duration, are supported by animation, images, text, and sound so that the mushroom material is more easily understood by users. This research is a type of research and development (R&D) using the ADDIE development model or a model with stages of analysis, design, development, implementation and evaluation. The subjects of this study were expert lecturers as subjects who assessed research instruments and tested the validity of learning videos on mushrooms. Biology teachers and X MIA 5 students at MAN 1 Makassar City as subjects who tested the practicality of mushroom learning videos. The results showed that the learning videos on mushrooms for class X students were valid and practical. The results of the validity value obtained were 4.5 (valid), and the practicality value obtained from the teacher's response was 90% (very practical). So, it can be concluded that the learning videos on mushroom material for class X students developed can be used and tend to improve student learning outcomes. Keywords: learning video, fungi, valid, and practical